Analysis of Marketing Strategies in Segmentation, Targeting, and Positioning (STP) in The Sales of Twelve SMPN 1 Pace Canteens - Darmawan, Andi Ihza (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: This study aims to analyze the process of segmentation, targeting, and positioning (STP) as a marketing strategy in the twelve canteen business. Design/Method/Approach: This research is a descriptive qualitative research, with a case study approach. This method is used to understand in depth about the opinions of each informant, so that the object of research can develop a more appropriate and effective strategy. Research Finding: This research is expected to provide strategic guidance to the twelve canteen businesses in developing more effective and targeted marketing strategies. By understanding market segments deeply, targeting effectively, and positioning products appropriately. Theoretical contribution/Originality:  Segmentation, Targeting, and Positioning (STP) is one of the marketing strategies that greatly affects business. Segmentation involves breaking the market into homogeneous groups, while targeting helps select potential market segments and, positioning creates a unique image for the product or brand in the minds of consumers. Practitionel/Policy implication: Segmentation, Targeting, and Positioning (STP) shows a company or business can target individual consumers more effectively, Implications can see market segmentation that has been targeted. Research limitation: limited informants as interviews for this research, so that misih is weak in the process of Segmentation, Targeting, and Positioning (STP). This research is applied to get input from other business people and the cutomers involved.